HUBUNGAN PROFESIONALISME PERAWAT TERHADAP KEPUASAN PASIEN DI RUANG RAWAT INAP UTAMA - Yetty Hardianty; Juniar Ernawaty; Febriana Sabrian (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Professional nursing services have the class and quality that providing satisfaction on the needs and desires more thancustomers or patients expected. This study aimed to find out the relationship of nurse professionalism and patientsatisfaction which was designed in descriptive correlational by applying cross- sectional approach. The sample in was84 respondents taken by using proportionate random sampling technique by fulfilling the inclusion criteria. Theinstrument used was a questionnaire that the content vailidity has been tested by three experts. The analyses used wereunivariate to know the frequency distribution and bivariate using alternative fisher exact test. The research findingshowed that there was a relationship between nurse profesionalism and patient satisfaction with p value (0,000) < α(0,1). Therefore, it can be concluded from the results of patient satisfaction questionnaires in hospitals that to improvethe quality of service, evaluation of the professional nurse is needed in order to achieve patient satisfication andincrease the quality of service in hospitals.Keyword: nurse, patient satisfactoni, profesionalism